Integrating Islamic Montessori in Digital Learning at Brainy Bunch Cyberjaya Malaysia - Hasanah, Adzkia Hulwia; Adawiyah, Siti Afifah; Zamry, Aina Fazleeny binti (el-Tarbawi, 2025)
Digital technology advancements have brought changes in the behavior and personality of school aged students. Especially in the use of gadgets, which tend to impact decreased learning motivation, concentration, and learning responsibility. However, in an international school, gadget use has become a directed learning tool through the integration of Islamic values and the Montessori approach. This study focuses on the development of student independence and discipline in gadget use at Brainy Bunch Cyberjaya, Malaysia. The data obtained through observation and interviews show that the development of student character at Brainy Bunch Cyberjaya Malaysia is carried out through habit formation, reinforcement of Islamic values, and management of gadget usage time, with consistent supervision from teachers. The findings of this study is parental involvement at home plays an important role in reinforcing the positive habits developed at school, thereby creating continuity between education at school and the family environment. This study has limitations as it was conducted in one school with a specific context, so the results cannot be generalized to all educational institutions.